PERBANDINGAN KONSENTRASI HIDROKOLOID DAN KONSENTRASI ASAM SITRAT DALAM MINUMAN JELI SUSU SESUAI MUTU DAN KUALITAS - Ade Heri Mulyati; Farida Nuraeni; Dini Restu Dwiyana (Universitas Pakuan, 2012)
In the manufacture of jelly milk drinks are necessary also other additional ingredients such as sugar is used as a sweetener in the manufacture of jelly while working to ease hydrocolloid dispersion. Potassium citrate is used for auxiliary materials, especially the formation of gel texture carrageenan, citric acid is used as a substance other than flavor in soft drinks, used also as an inhibitor of microbial growth in milk jelly drinks.An analysis of milk jelly beverage products, including the organoleptic analysis of where the testing is done against the panelists to determine the level of liking for the product. Viscosity to determine the viscosity of the product before the final product, the analysis is conducted to determine the strength of the gel on which the final product gel strength will be measured by looking at the gel fracture when pressed with a certain weight. PH measurement is necessary to know the level of acidity flavor obtained from addition of citric acid and then measuring ° brix to see the level of sweetness of the product because of sweetener used is pure sugar. In this study the analysis of protein levels because the products contain milk which is produced by converting nitrogen compounds into ammonium sulfate and then elaborated by NaOH, whereas the liberated ammonia was tied with H3BO4 and then titrated with HCl Key words: Gels, hydrocolloid, sugar, potassium citrate, citric acid, organoleptic, viscosity, gel strength, pH, ° brix, protein levels